LIMBAH TERNAK KELINCI SEBAGAI BAHAN BAKU PUPUK ORGANIK POTENSIAL - Risvan Anwar; Djatmiko Djatmiko (University of Prof. Dr. Hazairin, SH, 2018)
Many sources of raw materials which allegedly can enrich the nutrient content in the organic fertilizer. The weakness of organic fertilizer for this is the low level of nutrients contained in them.This study aims to determine the nutrient content contained in various combinations of organic fertilizer raw materials with rabbit animal waste as the main raw material.This study aims to determine the nutrient content in various combinations of organic fertilizer raw materials with rabbit animal waste as the main raw material. The experiment used a completely randomized design with raw materials as treatments, Livestock Waste Rabbit (LTK), Cow Manure (PKS) and Abu Straw Rice (AJP). Such treatment: B1 = LTK; B2 = LTK: PKS = 2: 1; B3 = LTK: AJP = 3: 1; B4 = LTK: PKS: AJP = 6: 2: 1; B5 = LTK: PKS: AJP = 5: 2: 1; B6 = LTK: PKS: AJP = 4: 2: 1; B7 = LTK: PKS: AJP = 3: 2: 1; B8 = LTK: PKS: AJP = 2: 2: 1; B9 = LTK: PKS: AJP = 1: 2: 1. The research concluded (a) Organic fertilizers are made from various materials raw has fulfilled SNI 19-7030-2004 about the specifications of Organic Waste Compost. (B) A combination of organic fertilizer raw materials significantly affect the nutrient content of manure. (C) Organic fertilizers expectations are: (a) Raw materials of animal wastes rabbit (LTK), (b) LTK: PKS: AJP = 6: 2: 1, (c) LTK: PKS: AJP = 2: 2: 1 and (d) LTK: PKS: AJP = 1: 2: 1.